Effects of high intensity morning exercise on afternoon performance in young hockey players - Rajalainen,V.; Korte, V.; Ahtiainen, J. (19th International Symposium "Modern Science and Practice for Strength and Endurance Training" October 10-12, 2018, 2020)
There are several studies suggesting that short but high intensity strength exercise in the morning improves performance in the afternoon (1). There are several different factors that could lead to performance benefits. Some authors have suggested performance benefits are due to higher afternoon testosterone levels after morning exercise, but also other mechanisms including body temperature and neural mechanisms are plausible (2). The aim of this study was to research whether power or maximal strength exercise performed in the morning affects performance in the afternoon within a 4-6-hour time window.